Anti-trypanosomal cadinanes synthesized by transannular cyclization of the natural sesquiterpene lactone nobilin. Issue 7 (1st April 2015) - De Mieri, Maria; Kaiser, Marcel; Brun, Reto; Thormann, Ursula; Imanidis, Georgios; Hamburger, Matthias
Graphical abstract: Abstract: Acid-catalyzed transannular cyclization of the germacrene-type sesquiterpene lactone nobilin1 was investigated with the aim of obtaining new anti-trypanosomal cadinane derivatives. The reaction was regiospecific in all tested reaction conditions. Compounds were fully characterized by spectroscopic and computational methods, and the anti-trypanosomal activity was evaluated and compared to nobilin (IC50 3.19 ± 1.69 μM). The tricyclic derivative11 showed most potent in vitro activity against Trypanosoma brucei rhodesiense bloodstream forms (IC50 0.46 ± 0.01 μM). Acid-catalyzed transannular cyclization of natural cyclodecadienes is an efficient strategy to generate new natural product derivatives with anti-protozoal activity.